Kepribadian Peserta Didik SMK di Kota Bandung selama Pandemi COVID-19 - Yusef Abdul Aziz; Desi Nur Utamillah (Journal of Education and Counseling (JECO), 2022)
The aim to be obtained is the personality profile of SMK students in the city of Bandung after the COVID-19 pandemic. The population involved SMK in Bandung City using purposive sampling technique involving 109 students and showing the results of a number of 28 students in the low category and 6 students in the very low category, so that 34 people were identified as "unhealthy" in the view of Gordon Allport's theory of personality. The data obtained from 34 students in the unhealthy personality category or about 31% of the total respondents, it is deemed necessary to have a solution as a preventive and curative form of the impact of the COVID-19 pandemic on education, especially vocational students in Bandung City, West Java.